Uma breve jornada de mim: uma narrativa reflexiva sobre a graduação de Medicina na Universidade Federal de São Carlos - Reinert, Gabriel Juvenal (Universidade Federal de São Carlos, 2024)
This reflective narrative encapsulates my transformative six-year journey pursuing a Medicine degree at São Carlos Federal University. Divided into three chapters mirroring classical teaching cycles, it succinctly captures key events, activities, and impactful moments in curricular and extracurricular realms. Ultimately, it underscores the realization that our choices and actions shape our destiny.
A Brief Journey of Myself: a Reflective Narrative on Medical Graduation at the Federal University of São Carlos
Keywords: Narrativa reflexiva; Reflective narrative; Educação médica; Medical education; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM